An Irish passion for justice the life of rebel New York attorney Paul O'Dwyer - Polner, Rob (Three Hills, Cornell University Press, 2024)
"This biography discusses Paul O'Dwyer, the brother of New York's last mayor of Irish descent, who in his own right as a lawyer and politician influenced the movements for labor rights, the creation of Israel, blacklist victims, civil rights, anti-Vietnam War protest, and the struggle for peace and justice in Northern Ireland"--